Chemotypes and antibacterial activity of Matricaria pubescens of Algeria (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Mekhadmi NE, Ramdani M, Lograda T, Chalard P, Figueredo G. 2019. Chemotypes and antibacterial activity of Matricaria pubescens of Algeria. Biodiversitas 20: 3170-3179. The objectives of this study were to determine the chemical composition and to evaluate the antibacterial activity of Matricaria pubescens L. essential oils from 14 sampling locations in southern Algeria. The extraction of essential oils was carried out by the hydro-distillation; the analysis of chemical composition of essential oil was carried out by GC-MS. Antibacterial activity was performed by disc diffusion method at the undiluted and diluted essential oil (1/1, 1:2, 1:4 and 1:8 v:v of DMSO) against eight species of bacteria (Bacillus cereus, Escherichia coli, Klebsiella pneumoniae, Listeria innocua, Proteus mirabilis, Pseudomonas aeruginosa, Salmonella enterica and Staphylococcus aureus). The results showed that the average yields of essential oils were 0.4 ± 0.27%. A total of 34 components were identified, averaging 99.22 ± 0.8% of the total oils. The main components were ?-ocimene (Z) (47.41 ± 13.67%), ?-pinene (19 ± 7.36%), ?-bulnesene (4.96 ± 10.6%), ocimene-allo (4.46 ± 1.3%), 1-phenyl-penta-2,4-diyne (4.06 ± 5.7%), limonene (3.84 ± 1.8%), caryophyllene oxide (2.36 ± 3.6%) and ?-bisabolene-E (2.08 ± 4.3%). Based on the UPGMA cluster analysis, there were two distinct clades of M. pubescens. This species has a chemical polymorphism with different chemotypes marked in nature. There were four chemotypes identified in the essential oil of M. pubescens in the region studied. The essential oil of M. pubescens has antibacterial activity against eight bacteria tested in a concentration-dependent manner.
Keywords: Algeria, antibacterial activity, chemotypes, essential oils, Matricaria pubescens